How HRD, Servant Leadership, and Good Governance Improve Islamic Bank Staff Performance and Morale - Nur Hilal; Hariyanto R. Djatola; Ananda Sabil Hussein (APMBA (Asia Pacific Management and Business Application), 2023)
This research was conducted to analyse the impact of human resource (HR) development, servant leadership, and good governance on employee performance and moral commitment in Islamic banking. Using quantitative approach data through a questionnaire with 215 respondents were collected as the primary data. This research was conducted from July to September 2022. The data obtained was carried out in the analysis stage using the structural equation modeling (SEM) AMOS program. The results of this study indicate that HR development has a positive and insignificant effect on moral commitment; servant leadership and good governance have a positive and significant effect on moral commitment; HR development has a positive and insignificant effect on employee performance in Islamic banking; servant leadership, good governance, and moral commitment have a positive and significant effect on employee performance in Islamic banking; while the role of moral commitment has a positive and insignificant effect on HR development on employee performance; and servant leadership and good governance have a positive and significant effect on employee performance through moral commitment.